2005
DOI: 10.1103/physrevd.71.074007
|View full text |Cite
|
Sign up to set email alerts
|

Description of gluon propagation in the presence of anA2condensate

Abstract: There is a good deal of current interest in the condensate < A a µ A µ a > which has been seen to play an important role in calculations which make use of the operator product expansion.That development has led to the publication of a large number of papers which discuss how that condensate could play a role in a gauge-invariant formulation. In the present work we consider gluon propagation in the presence of such a condensate which we assume to be present in the vacuum. We show that the gluon propagator has n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
50
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 38 publications
3
50
1
4
Order By: Relevance
“…Moreover, the inclusion of a small number of dynamical quarks ('unquenching') produces a relative suppression to the gluon propagator, but preserves the feature of saturation clearly intact [10]. Naturally, these results have attracted particular attention, since they offer a valuable opportunity to explore the nonperturbative dynamics of Yang-Mills theories, and even though some of the underlying ideas have a rather long history [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], various field-theoretic mechanisms that may account for this characteristic behavior have been considered in the more recent literature .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the inclusion of a small number of dynamical quarks ('unquenching') produces a relative suppression to the gluon propagator, but preserves the feature of saturation clearly intact [10]. Naturally, these results have attracted particular attention, since they offer a valuable opportunity to explore the nonperturbative dynamics of Yang-Mills theories, and even though some of the underlying ideas have a rather long history [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], various field-theoretic mechanisms that may account for this characteristic behavior have been considered in the more recent literature .…”
Section: Introductionmentioning
confidence: 99%
“…Apart from appearances and applications in many other fields of physics, vector backgrounds can be used in order to incorporate mass dimension two vector condensates into gauge field theories in a Lorentz invariant way [1,2,3] or, in a different context, in theories breaking Lorentz invariance explicitely [4]. The latter approach is motivated from string [5] and non-commutative field theory [6].…”
Section: Introductionmentioning
confidence: 99%
“…A Lorentz invariant ensemble is a set of vectors which is mapped onto itself under any Lorentz transformation, while, of course, almost every single element changes. In [1,2,3] it has been demonstrated that the elementary fermions and/or bosons are removed from the spectrum of asymptotically freely propagating particles. Usually the ensembles of backgrounds used in the literature [2,3] contain gauge field configurations leading to zero as well as to non-zero field tensors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations